Prevalence of Injuries at Grassroots Football Festival Under 12 - Effendy, Amri Luthfan; Hanief, Yulingga Nanda (Journal of Sport and Exercise Science, 2025)
Purpose: This research aims to determine the prevalence and types of injuries experienced by young athletes aged 12 years in the Grassroot Football Festival Under 12 football tournament and the factors that cause them. Materials and Methods: The research method was descriptive quantitative with a survey approach. The study population was players from 24 teams participating in the tournament, with a purposive sampling technique that resulted in 24 respondents. Data was collected through a questionnaire that included information on the type of injury, injury location, causal factors, and first treatment. The analysis approach used is percentage analysis. Result: The results showed that the most common injury was bruising (38%), mainly to the lower extremities, namely the lower legs (21%). Most injuries occurred due to physical contact (83%), with a higher percentage of injuries in the second half (63%) possibly due to fatigue. Although most athletes could continue the match after the injury, they required treatment from the coach as a first-aid provider (92%). Conclusion: The predominant type of injury in young athletes was bruising caused by physical contact, particularly the lower limbs, and mainly occurred in the second half. These findings highlight the important role of the coach in injury management and the need for injury prevention programs, such as FIFA 11+ Kids, to reduce the risk of injury among young athletes.